Industrial Enlightenment : Science, technology and culture in Birmingham and the West Midlands 1760-1820. - Jones, Peter M. (Manchester University Press, 2017)
Industrial Enlightenment' explores the transition through which England passed between 1760 and 1820 on the way to becoming the world's first industrialised nation. In drawing attention to the important role played by scientific knowledge, it focuses on a dimension of this transition which is often overlooked by historians. The book argues that in certain favoured regions, England underwent a process whereby useful knowledge was fused with technological 'know how' to produce the condition described here as Industrial Enlightenment. At the forefront of the process were the natural philosophers.